Under Siege : Journal Publishing in the 1990s - McCullough, Karen M. (ARCTIC, 1995)
Budget cutbacks are the theme of the '90s, and all aspects of advanced education are under intense pressure from severely reduced federal and provincial funding. The realm of scholarly communication is no exception. At a time of rising production costs, reduced postal subsidies, and subscription cancellations from under-funded university libraries, publishers of scholarly journals are now faced with the outright elimination of funding sources such as the Scientific Publication Grants Program of the Natural Sciences and Engineering Research Council of Canada (NSERC). According to NSERC, the support of scientific journals is a "non-core program" and is therefore being terminated to allow more funding to be directed to research grants. It is difficult to understand how the dissemination of knowledge came to be defined as a non-core program. The goal of ensuring adequate funds for the direct costs of conducting research is certainly laudable. Nevertheless, the loss, through inadequate funding, of scholarly journals as a major forum for scientists to communicate the results of their work has serious consequences for the entire scientific endeavour. There is little point in funding research that will remain unknown to the broader academic community and to Canadian tax-payers who support that community. Such a move could easily result in the research being available only to a privileged few (relatively speaking) through informal networks of communication such as the Internet. . The move to on-line publishing may somewhat ease the budgetary pressures on journal support programs and university libraries as more and more new journals are offered directly in the electronic media rather than in print. . Until such time as the print journal has disappeared, publishers will continue to seek ways to make the production process as efficient and cost-effective as possible, while maintaining the quality and integrity of scholarly journals. . Fiscally responsible journal management means maintaining subscriber rates that will ...